2020
DOI: 10.1016/j.chest.2019.09.016
|View full text |Cite
|
Sign up to set email alerts
|

County-Level Variations in Receipt of Surgery for Early-Stage Non-small Cell Lung Cancer in the United States

Abstract: BACKGROUND: Although counties are the smallest geographic level for comprehensive healthcare delivery analysis, little is known about county-level variations in receipt of curativeintent surgery for early-stage non-small cell lung cancer (NSCLC) and factors contributing to such variations in the United States.METHODS: A total of 179,189 patients aged $ 35 years who were diagnosed with stage I to II NSCLC between 2007 and 2014 in 2,263 counties were identified from 39 states, the District of Columbia, and Detro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 41 publications
4
22
0
Order By: Relevance
“…Prior studies have reported the marked heterogeneity in these potentially modifiable factors across counties, and this heterogeneity may have partially contributed to socioeconomic inequalities in mortality. 46,47 Results of correlation analysis imply that these modifiable factors were linked to socioeconomic inequalities in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported the marked heterogeneity in these potentially modifiable factors across counties, and this heterogeneity may have partially contributed to socioeconomic inequalities in mortality. 46,47 Results of correlation analysis imply that these modifiable factors were linked to socioeconomic inequalities in mortality.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study of >441,000 individuals diagnosed with any histologic subtype of lung cancer between 2010 and 2014, the receipt of guideline‐concordant treatment was lower among Black (odds ratio [OR], 0.78; 95% confidence interval [CI], 0.76‐0.80) and Hispanic (OR, 0.94; 95% CI, 0.90‐0.98) people compared with White people 92 . Another study of approximately 180,000 individuals who had early stage nonsmall cell lung cancer diagnosed between 2007 and 2014 showed substantial variation in the receipt of curative‐intent surgery across counties, with the lowest rates in counties that had a high proportion of Black people who had nonsmall cell lung cancer or a high poverty or uninsured rate, and in nonmetropolitan areas 93 …”
Section: Factors That Contribute To Cancer Disparities Across the Can...mentioning
confidence: 99%
“…However, these differences have narrowed in recent years (12,13). Black patients still present with more advanced disease than their White counterparts (14,15). When accounting for the stage at presentation and other factors, Black patients still have lower five-year survival for local disease than their White counterparts.…”
Section: Introductionmentioning
confidence: 99%